Towards supporting scholarship in research by clinical pharmacy faculty - Pickard AS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Objective: The objective of this study was to assess the need for research support, faculty development, and topics of interest to clinical track pharmacy faculty that would facilitate scholarship in research.Methods: A cross-sectional survey of pharmacy practice-based faculty at University of Illinois at Chicago (UIC) completed via the web in November 2005.Results: Of 39 clinical track faculty respondents (48% response rate), 100% indicated they were interested in being co-investigator or 77% lead investigator on a research grant proposal. The majority of respondents expressed "a lot" or "extreme" interest in receiving methodological guidance and administrative support in order to pursue research interests. The greatest interest in research support services related to sample size calculations, selection of appropriate statistical tests, grant writing, and writing for journals. Barriers to research cited by faculty included lack of confidence in ability, the need for balancing responsibilities, and reward for efforts. Suggestions included the creation of specific research interest groups, research seminars, formal mentoring and statistical support services.Conclusions: Clinical-track faculty are interested in research-related scholarship but typically lack the confidence or skills to lead research. While this study was limited to UIC clinical faculty, UIC faculty are attracted from Colleges of Pharmacy across North America and it is notable that such barriers can be quickly identified using a brief web-based survey in order to inform a plan that provides resources and support for research by clinical pharmacy faculty.